Dietary supplementation with calcium propionate could beneficially alter rectal microbial composition of early lactation dairy cows - Zhang, Fan; Zhao, Yiguang; Wang, Yue; Wang, Hui; Nan, Xuemei; Guo, Yuming; Xiong, Benhai (Frontiers in Veterinary Science, 2022)
Dietary supplementation with calcium propionate can effectively alleviate negative energy balance and hypocalcemia of dairy cows in early lactation. The objective of this study was to investigate the effects of calcium propionate feeding levels on the immune function, liver function, and fecal microbial composition of dairy cows in early lactation. Thirty-two multiparous Holstein cows were randomly assigned to four treatments after calving. Treatments were a basal diet plus 0 g, 200 g, 350 g, and 500 g calcium propionate per cow per day throughout a 5-week trial period. Cows were milked three times a day, and blood was sampled to measure immune function and liver function on d 7, 21, and 35. The rectal contents were sampled and collected on d 35 to analyze the microbial composition using 16S rRNA gene sequencing. The results indicated that increasing amounts of calcium propionate linearly increased the concentration of malondialdehyde in serum. We detected no differences in the serum concentrations of total protein, IgG, IgM and calcium, but the concentrations of albumin and IgA changed quadratically. With the increase of calcium propionate, the activity of serum alanine transaminase and aspartate aminotransferase increased linearly, in contrast, the activity of alkaline phosphatase decreased linearly. Moreover, dietary supplementation with increasing levels of calcium propionate tended to quadratically decrease the relative abundance of Firmicutes while quadratically increased the abundance of Bacteroidetes, and consequently linearly decreased the Firmicutes/Bacteroidetes ratio in the rectal microbiota. Additionally, the supplementation of calcium propionate increased the relative abundances of Ruminococcaceae_UCG-005 and Prevotellaceae_UCG-004 linearly, and Ruminococcaceae_UCG-014 quadratically, but decreased the relative abundances of Lachnospiraceae_NK3A20_group and Family_XIII_AD3011_group quadratically. Compared with the CON group, the calcium propionate supplementation significantly decreased the relative abundance of Acetitomaculum but increased the abundances of Rikenellaceae_RC9_gut_group and Alistipes. In summary, these results suggested that the supplementation of calcium propionate to dairy cows in early lactation could beneficially alter the rectal microbiota.